Evaluation of the university professor and recognition needs: analysis and relationship - Scattolon Huapaya, Luciano Carlos Andrés (2020)
This research was carried out with the objective of analyzing the relationship between the evaluation of the university professor and the satisfaction of recognition needs. It is a non-experimental inductive study, of a descriptive and correlational type of mixed approach. The sample consisted of a total of 28 professors from the English area of the main campus of a Private University of Lima, in the 2018- II cycle, using a probabilistic sampling for convenience. The questionnaire was conducted as an instrument and the survey as a technique. The system used by the university shows evidence of relating positively to the recognition needs of the university teacher; the study has contributed with the verification of processes and tools applied to the evaluation and the impact on the collaborator specifically in their satisfaction of needs, oriented to generate an added value for the educational service offer that represents a competitive differential in the current global context.